Pola Dan Peta Kemampuan Keuangan Desa Setelah Penerbitan Undang-Undang Nomor 6 Tahun 2014 Tentang Desa - Karyada, I Putu Fery; Ayu, Putu Cita; Mahayasa, I Gede Arya (E-Jurnal Akuntansi; Vol 30 No 3 (2020), 2020)
This study examines the impact of Dana Desa on village relations and financial ability. The relation is determined by village independence, whereas the financial ability to know village capability in their need. The method is descriptive using tables and graphs. Object analysis is APBdes from 2016 to 2018. Samples are Jembrana, Tabanan, Gianyar and Klungkung regency. Based on the result, all villages in Jembrana, Tabanan, Gianyar, and Klungkung have a ratio of fewer than 25 points so in the instructive category. Growth and Share analysis get 1 village in quadrant I, 3 villages in quadrant II, 5 villages in quadrant III and 282 villages in quadrant IV. Keywords: Pattern; Financial Ability; Dana Desa; Village.